Mineral processing plant design, practice, and control proceedings - Mular, Andrew L.; Halbe, D. N.; Barratt, Derek J. 1939- (Society for Mining, Metallurgy, and Exploration, 2002)
Mineral Processing Planet Design, Practice, and Control is a new standard text for university-level instruction and a valuable guidebook for operators considering new construction, renovations, or expansions. Most of all, it's practical, quick reference for engineers, consultants, suppliers, manufacturers, or anyone involved in the design or operation of a minerals processing plant.
Keywords: Ore-dressing plants -- Design and construction -- Congresses.; elektronické knihy; electronic books